THE URGENCY OF LEARNING ARABIC IN IMPROVING THE QUALITY OF HUMAN RESOURCES IN INDONESIA - Agus Yasin; Riska Hanan Nurahmah; Jamal Jamal (Sean Institute, 2023)
Globalization facilitates people's access to a wide range of information through modernity and technology. Qualified human resources are the key to success in the globalization era, and foreign language proficiency is required. Using a qualitative approach based on a literature review, this study investigates the importance of learning Arabic for the quality of human resources. The findings of this study validate that studying Arabic may improve the quality of human resources. Not only that, but being the country with the most Muslims in the world, Indonesians have the opportunity to sharpen and expand their relationships with Allah.